Partisipasi Masyarakat Dalam Program Pembangunan - Rodi Wahyudi (Kutubkhanah, 2012)
Various efforts and strategies have been mobilized and utilized to intensify rural development in order to reduce imbalance between rural and urban areas. Rural community development is a process to improve quality of life by developing all aspects of human. The most important factors in processes of rural community development is type of programs, community participation and communities values . This article aim to how and why Kampung Kundang, Selangor, Malaysia have been successful and awarded as Excellent Village (Desa Cemerlang). This rural community initiates and participates in agro-based income generating activities, small and home based industries. The government agency provide training, financial funding, land field rent and basic infrastructures. The most significant social values in this successful community development process named as “guyub”. “Guyub” is peaceful value, trust, harmony, sincere love and cooperativeness, which motivate this community involvement in the development process.